Analisis Tantangan Bahasa dan Budaya dalam Penerjemahan Teks Arab di Media Sosial - nurfasilah; Pangulian Harahap; Rana Khairiyyah; Sahkholid Nasution (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2024)
The rapid development of digital technology has expanded cultural access and interaction through various social media platforms. However, in the context of translating Arabic texts into other languages, significant challenges arise from linguistic and cultural differences that affect the overall understanding of the message. This article explores the challenges faced by translators in preserving the original meaning of Arabic texts when adapting them to social media, focusing on language and cultural aspects. Using a literature review method, this study analyzes relevant research on translation and cross-cultural communication. Findings indicate that differences in language structure, idioms, and cultural values can hinder the translation process, often leading to meaning distortions or misinterpretations among readers. Additionally, the space and format limitations on social media add further challenges for translators in selecting words and styles that convey the original message accurately. This article provides an in-depth understanding of the importance of cultural sensitivity in translating Arabic texts in the digital age and highlights strategies that can be used to address these challenges. Keywords : Arabic Text Translation, Cross-Cultural Challenges, Social Media, Language